Pregnancy and cardiovascular outcomes among patients post Fontan surgery: a 25-year single-centre retrospective cohort study - Ran Kornowski; Eran Hadar; Daniel Yehuda; Omri Soudry; Eyal Schwartz; Ilan Richter; Alexander Dadashev; Shahar Vig; Shimon Kolker; Ohad Houri; Rafael Hirsch; Nili Schamroth Pravda (Open Heart)
Introduction Data on the characteristics and outcomes of pregnancy and among patients with Fontan physiology are limited. We aimed to evaluate the immediate and long-term outcomes among these patients who were followed at our centre.Methods We included adult patients who had undergone Fontan surgery for congenital heart disease and were pregnant between 1994 and 2021. We examined maternal and obstetric outcomes.Results In a cohort of 109 patients following Fontan procedure, 51 patients were women, and 19 patients (37%) had a pregnancy during the follow-up period, accounting for a total of 46 pregnancies. Intrauterine growth retardation of the fetus was common, observed in 23% of all pregnancies and 50% of live births. The main fetal complication was prematurity, observed in 43% of all pregnancies and 90% of live birth. The maternal complications included pre-eclampsia (one patient), placental detachment (one patient), acute heart failure exacerbation (one patient), arrhythmia (three atrial arrhythmias) and major peripartum haemorrhage (two patients), with no peripartum death.Conclusions Over one-third of women with Fontan physiology in our cohort had a documented pregnancy. Maternal and obstetric complications were common among these patients, and expanded long-term data is needed. Limitations, including small sample size and survival bias, may have underestimated the risk of adverse outcomes in this cohort.